2005
DOI: 10.1128/jvi.79.17.11105-11114.2005
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of p53 by Double-Stranded RNA Modulates the Antiviral Response

Abstract: p53 has been well characterized as a tumor suppressor gene, but its role in antiviral defense remains unclear. A recent report has demonstrated that p53 can be induced by interferons and is activated after vesicular stomatitis virus (VSV) infection. We observed that different nononcogenic viruses, including encephalomyocarditis virus (EMCV) and human parainfluenza virus type 3 (HPIV3), induced down-regulation of p53 in infected cells. Double-stranded RNA (dsRNA) and a mutant vaccinia virus lacking the dsRNA bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 43 publications
2
56
0
Order By: Relevance
“…It has been proposed that PKR mediates apoptosis at the transcriptional level. For example, PKR signals through STAT1 and STAT3 (36,43,44), interferon regulatory factor 1 (IRF1) (16,45), IRF3 (46), p53 (17,47,48), and the IKK complex to regulate transcription during proinflammatory (16,17,40,45) and/or proapoptotic responses (12,40,45,49). PKR-dependent apoptosis was also associated with Fas-associated death domain (FADD)-mediated activation of caspase 8 (50,51) and up-regulation of Fas and Bax (18,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that PKR mediates apoptosis at the transcriptional level. For example, PKR signals through STAT1 and STAT3 (36,43,44), interferon regulatory factor 1 (IRF1) (16,45), IRF3 (46), p53 (17,47,48), and the IKK complex to regulate transcription during proinflammatory (16,17,40,45) and/or proapoptotic responses (12,40,45,49). PKR-dependent apoptosis was also associated with Fas-associated death domain (FADD)-mediated activation of caspase 8 (50,51) and up-regulation of Fas and Bax (18,52,53).…”
Section: Discussionmentioning
confidence: 99%
“…The role of p53 in virus-induced apoptosis remains controversial. Thus, the finding that vesicular stomatis virus (VSV) infection can activate the p53 protein (Takaoka et al, 2003) suggests that p53 may play a role in virus-induced apoptosis, whereas on the other hand, destabilization of the p53 reported during ssRNA virus infection suggests that p53 degradation may facilitate apoptosis induced by ssRNA viruses (Marques et al, 2005). Both viral dsRNA and viral DNA have been shown, however, to induce apoptosis by mechanisms independent of both IFNs and p53 (Weaver et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…PKR is one of the best-characterized protein kinases and is involved both in IFN-mediated antiviral activity (18) and in IFNmediated anti-oncogenic activity (14,16). Recently, it also was found that PKR or viral dsRNA down-regulates p53 (19,20). Although the biological functions of PKR have been evaluated, it remains unclear whether the induction of PKR expression is exclusively dependent on type I IFN.…”
mentioning
confidence: 99%